Efficient synthesis of the C(7)–C(20) subunit of amphidinolides C and F - Mahapatra, Subham (2009)
Synthesis of the C(7)–C(20) subunit of amphidinolides C and F has been accomplished utilizing a Me(3)Al-mediated ring opening of a vinyl iodide/allylic epoxide to establish the C(12,13) anti stereochemistry, an organolithium coupling/olefination sequence to construct the C(9)–C(11) diene moiety and a sulfone alkylation/hydroxylation strategy to join the C(7)–C(14) and C(15)–C(20) fragments.